2013
DOI: 10.3389/fmicb.2013.00037
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in the deep-subsurface hydrothermal aquifer feeding the giant gypsum crystal-bearing Naica Mine, Mexico

Abstract: The Naica Mine in northern Mexico is famous for its giant gypsum crystals, which may reach up to 11 m long and contain fluid inclusions that might have captured microorganisms during their formation. These crystals formed under particularly stable geochemical conditions in cavities filled by low salinity hydrothermal water at 54–58°C. We have explored the microbial diversity associated to these deep, saline hydrothermal waters collected in the deepest (ca. 700–760 m) mineshafts by amplifying, cloning and seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 66 publications
4
14
0
Order By: Relevance
“…Noteworthily, sequences related to Delftia comprised the majority of RNA library from a borehole in Pyhäsalmi mine (Finland) representing the main active part of the microbial community (Miettinen et al, 2015). Similar sequences have been recovered from saline hydrothermal water in a Mexican mine (Ragon et al, 2013). Another minor component of the 3P well community—bacteria of the genus Desulfotomaculum —appeared in August 2009, both in water samples and in the enrichment culture with cellobiose and sulfate; they were also detected in June 2011 by 16S rRNA gene fragments pyrosequencing analysis.…”
Section: Discussionsupporting
confidence: 69%
“…Noteworthily, sequences related to Delftia comprised the majority of RNA library from a borehole in Pyhäsalmi mine (Finland) representing the main active part of the microbial community (Miettinen et al, 2015). Similar sequences have been recovered from saline hydrothermal water in a Mexican mine (Ragon et al, 2013). Another minor component of the 3P well community—bacteria of the genus Desulfotomaculum —appeared in August 2009, both in water samples and in the enrichment culture with cellobiose and sulfate; they were also detected in June 2011 by 16S rRNA gene fragments pyrosequencing analysis.…”
Section: Discussionsupporting
confidence: 69%
“…There are so far no cultured representatives from this group and their metabolic potential remains elusive. 16S rRNA gene information revealed that candidate division OP3 belongs to the Planctomycetes/Verrucomicrobia/Clamydiae (PVC) superphylum and it was suggested that members of this group are most likely anaerobes thriving in marine sediments, lakes, and aquifers (Glöckner et al., ; Ragon, Van Driessche, Garcia Ruiz, Moreira, & Lopez‐Garcia, ). Currently available genome information obtained from single cells and a waste water treatment plant for members of this group, provisionally named Omnitrophica , revealed the presence of genes coding for respiratory nitrate reductase, heme/copper‐type cytochrome/quinol oxidases, and nitric oxide reductases (Speth, In ‘t Zandt, Guerrero‐Cruz, Dutilh, Jetten, ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we observed slightly higher abundances of archaea in the lower aquifer, dominated by putative ammonia‐oxidizing Thaumarchaeota . Similarly, ammonia oxidizers also formed a substantial fraction of the archaeal community in 760 m depth of a hydrothermal gypsum aquifer in a recent study in Mexico (Ragon et al ., ).…”
Section: Discussionmentioning
confidence: 97%